2012
DOI: 10.3149/fth.1002.178
|View full text |Cite
|
Sign up to set email alerts
|

Latino Immigrant Differences in Father Involvement with Infants

Abstract: The relationship between Latino fathers' immigrant status and their involvement with their 12-month-old infants was examined using the Fragile Families data set, a longitudinal birth cohort study. We examined differences among 787 immigrant and nonimmigrant Latino fathers along three dimensions of father involvementaccessibility, engagement, and caretaking, as reported by both mothers and fathers. First generation immigrant fathers were more accessible to their infants, but showed lower levels of engagement wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Similar patterns may be observed in infancy; levels of paternal engagement in the current study were highest for active behaviors (taking the baby out and playing with the baby) and lowest for conventional caregiving activities (bathing, diapering). Fathers’ traditional gender role attitudes may also contribute to lower levels of paternal involvement in tasks commonly considered to be “feminine” or completed by mothers (D’Angelo et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar patterns may be observed in infancy; levels of paternal engagement in the current study were highest for active behaviors (taking the baby out and playing with the baby) and lowest for conventional caregiving activities (bathing, diapering). Fathers’ traditional gender role attitudes may also contribute to lower levels of paternal involvement in tasks commonly considered to be “feminine” or completed by mothers (D’Angelo et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Although the focus on low-income, Mexican origin families was deliberate in order to expand fathering research to an understudied population, results cannot be generalized to other racial, ethnic, or socioeconomic groups. The current study included both Mexico- and United States-born parents and prior research has suggested an effect of immigrant status on fathering (D’Angelo et al, 2012). Additional research is needed to evaluate the extent to which the underlying structure and correlates of fathering differ by country of birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, examination of the experiences of transnational fathers is limited by largely comparative research which views immigrant families through a lens of cultural and developmental deficits (Strier and Roer-Strier 2010). Although some research considers the social contexts of fatherhood, research addressing Latino fatherhood in the U.S., is limited (D'Angelo et al 2012;Guendelman et al 2018;Parra-Cardona et al 2006;Taylor and Behnke 2005). This dearth of research is problematic as Latinos are one of the largest minority populations in the U.S. making up almost 18% of the total population (Flores et al 2017).…”
Section: Transnational Familiesmentioning
confidence: 99%
“…Latino men face a unique set of challenges related to cultural values: the value of familismo (familial ideals) may facilitate fathers’ connections to their children, but the heavy emphasis on machismo (masculine ideals) may undermine these connections. Latino fathers who craft a “hybrid” (or bicultural) style of parenting are more likely to be involved and nurturing fathers and have higher quality father–child and father–mother relationships (Cabrera & Bradley, ; see also Cruz et al., ; D'Angelo, Palacios, & Chase‐Lansdale, ). Additionally, undocumented Latino fathers encounter barriers that prevent their involvement in children's lives, including being hesitant to attend school functions because they feel unwelcome, are unfamiliar with the language, and fear deportation (Cabrera, Aldoney, & Tamis‐LeMonda, ; Jimenez‐Castellanos & Gonzalez, ).…”
Section: Parenting and Men's Development And Identity In Young Adulthoodmentioning
confidence: 99%